Algebraizations of Propositional Logic and Monadic Logic (Indian Journal of Advanced Mathematics (IJAM), 2024)
In this paper, we introduce the language systems of propositional logic (LSPL), which involves no variables, and monadic predicate logic (LSMPL), which consists of predicates applied to single variables. We review the validity and dedication related to (LSPL) and (LSMPL) with their properties. After that, we investigate the connection between Boolean algebras with (LSPL) and (LSMPL) to make algebraizations methods out of logic.